2018
DOI: 10.33143/jhtm.v3i2.1020
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Baiturrahman Kota Banda Aceh

Abstract: AbstrakStunting atau pendek merupakan indikator status gizi kronis yang dapat menggambarkan pertumbuhan yang tidak optimal karena malnutrisi jangka panjang. Dinkes kota Banda Aceh menemukan prevelensi angka stunting pada balita di tahun 2016 menjadi 27,1%. stunting  pada balita di Kota banda Aceh masih menjadi masalah masyarakat. Tujuan Penelitian : Untuk mengetahui faktor-faktor yang mempengaruhi kejadian stunting pada balita di wilayah kerja puskesmas Baiturrahman  Kota Banda Aceh tahun 2018. Metode  Penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Danila (2019), concluded that there was a significant relationship between the incidence of stunting and geographical conditions such as population density and area of residence in Manggarai Regency. According to research by Aridiyah et al (2015), the factor that most influences the occurrence of stunting in children under the age of five in rural and urban areas is the level of zinc adequacy (Danila et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Danila (2019), concluded that there was a significant relationship between the incidence of stunting and geographical conditions such as population density and area of residence in Manggarai Regency. According to research by Aridiyah et al (2015), the factor that most influences the occurrence of stunting in children under the age of five in rural and urban areas is the level of zinc adequacy (Danila et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Community socioeconomic conditions, characteristics of mothers during pregnancy, access to health services, antenatal care, and parenting, as well as the environment and geographical conditions (population density, climatic conditions, and inadequate sanitation), are all factors (Erniawati & Kamaruddin, 2020). Stunting is thus a predictor of poor human resource quality, which will further impede the development of the nation's potential, as nutrition from childhood to adolescence has a profound effect on healthy growth (Aridiyah et al, 2015;Delara et al, 2012).…”
Section: Government Countermeasures Include Specific Interventions Ca...mentioning
confidence: 99%
“…Anak yang mengalami stunting berpeluang memiliki IQ non-verbal dibawah 89 dan IQ lebih rendah 4,57 kali dibandingkan IQ anak yang tidak stunting pada peride 2 tahun pertama kehidupan (Daracantika, Ainin, & Besral, 2021). Stunting dipengaruhi faktor antara lain asupan protein, pemberian ASI eksklusif, BBLR, status gizi, infeksi (Abdullah & Sari, 2018;Ruswati et al, 2021). Pendidikan dan pemahaman keluarga tentang gizi, tingkat pendapatan, budaya terkait pembatasan jenis makanan terutama ikan dan telur, rendahnya aksesibilitas, kurangnya kesadaran keluarga mengatasi masalah gizi buruk berdampak terhadap kejadian stunting (Patty & Nugroho, 2019).…”
Section: Introductionunclassified
“…Male children are also more at risk of stunting than female children (11). Health services are also one of the factors that influence the incidence of stunting (12).…”
Section: Introductionmentioning
confidence: 99%